Towards an uncertain future? The strengthening of Japan's autonomy in Asia-Pacific - Miyamoto,Shiguenoli (2014)
Recently, Japan has been increasing tensions with China regarding the Pinnacle Senkaku/Diaoyu islands. Due to the Chinese military development, Japan has been working on its political and military strengthening in Asia. This essay presents two possible scenarios for Japan.